2020
DOI: 10.33448/rsd-v9i11.9170
|View full text |Cite
|
Sign up to set email alerts
|

Análise do perfil epidemiológico dos casos de leishmaniose visceral no estado do Piauí no período de 2009 a 2018

Abstract: A Leishmaniose Visceral (LV) é uma antropozoonose de alta letalidade, pode causar a morte em 90% dos casos não tratados, caracteriza-se por febre e hepatoesplenomegalia. É causada por protozoários da espécie Leishmania infantum chagasi e transmitida pelo flebotomíneo. No presente estudo fez-se a análise epidemiológica dos casos notificados no Piauí utilizando-se os dados obtidos do Sistema de Informação de Agravos de Notificação (SINAN) no período de 2009 a 2018. A quantidade de casos de LV no Piauí é de 2 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
1
0
5
Order By: Relevance
“…In addition, the average incidence found in the period with the lowest number of cases (2017-2021) is considered high equaling those found in the north and northeast regions, where VL has the highest incidence (Araújo, 2017) It was observed that almost 60% of VL cases in the city occurred in male individuals, maintaining this percentage in all evaluated periods. Studies on the incidence of VL in other cities in the country also point to a greater susceptibility of men to the disease, with a percentage between 58 and 75% of cases (Rodrigues et al, 2020;Souza et al, 2018;Rocha et al, 2018;Lisboa et al, 2016;Araújo, 2016;Ortiz et al, 2015). It is considered that the greater exposure of men to sources of contamination, due to the performance of occupational and behavioral activities as well as hormonal factors are responsible for this higher percentage of infection (Ortiz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average incidence found in the period with the lowest number of cases (2017-2021) is considered high equaling those found in the north and northeast regions, where VL has the highest incidence (Araújo, 2017) It was observed that almost 60% of VL cases in the city occurred in male individuals, maintaining this percentage in all evaluated periods. Studies on the incidence of VL in other cities in the country also point to a greater susceptibility of men to the disease, with a percentage between 58 and 75% of cases (Rodrigues et al, 2020;Souza et al, 2018;Rocha et al, 2018;Lisboa et al, 2016;Araújo, 2016;Ortiz et al, 2015). It is considered that the greater exposure of men to sources of contamination, due to the performance of occupational and behavioral activities as well as hormonal factors are responsible for this higher percentage of infection (Ortiz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A forma clássica de transmissão da esporotricose ocorre a partir da inoculação traumática do fungo no tecido subcutâneo (RODRIGUES et al, 2020). O fungo é amplamente encontrado na natureza e pode ser identificado no solo, vegetais, madeira em decomposição e na água (KAUFFMAN et al, 2022).…”
Section: Transmissãounclassified
“…Posto isto, a doença usualmente predomina em pessoas que exercem atividades ocupacionais de risco, como o cultivo da terra e jardinagem, principalmente em áreas rurais (FURTADO et al, 2019). Esse tipo de transmissão por meio de contato direto com o solo é chamado de via sapronótica (RODRIGUES et al, 2020).…”
Section: Transmissãounclassified
“…Dentre os animais mais comumente relacionados a infecção pelo fungo, os gatos são os mais afetados (RODRIGUES et al, 2020). Devido à proximidade dos gatos domésticos com seus donos, esses animais possuem um papel importante na emergência dos casos de esporotricose humana.…”
Section: Transmissãounclassified
See 1 more Smart Citation